Optimal design of bread baking: Numerical investigation on combined convective and infrared heating - Purlis, Emmanuel (2014)
This paper presents a theoretical approach for optimal design focused on baking, which is based on knowledge about transport phenomena and physicochemical changes occurring during the process. Such approach consists in identifying and defining the critical and quality times of the process, and to find a technological solution to make equal those times. Then, an optimum process presents the same critical and quality times. As case of study, the conventional bread baking process is analysed, where the critical time is the time necessary to complete the dough/crumb transformation, while the quality time is given by the target value of browning development. The use of infrared heating as additional energy source, besides convection and radiation, is proposed here to obtain optimum processes. The proposed solution gives good results in comparison with conventional baking, improving process outputs such as baking time, weight loss, thermal input, and energy input. Finally, the generalisation of the approach is discussed.